Pressure Groups and democracy in India - "Misquitta, L P" (New Delhi, 1991)
I have been fascinated with the working of pressure groups. The phenomenon of pressure groups is an organised sense is new, specially in India. However, in everyday life, we can easily see groups of people applying pressure on public policies and actions for diverse reasons.
Keywords: Political Science